Analysis of the Influence of Selection Quality on Competence: Intrinsic Motivation and Integrity as Mediation - wibowo, wawan tri (LPPM Universitas Trunojoyo Madura, 2025)
This study aims to analyze the influence of selection quality on employee competencies with intrinsic motivation and integrity as mediating variables. This research method was carried out at the Yogyakarta Police with a sample of 148 respondents, using a questionnaire prepared on a Likert scale of 1 to 5, to measure how much the causality relationship between selection quality variables, integrity, intrinsic motivation, and competence was analyzed using AMOS SEM. The results of the study show that the quality of selection has a positive and significant effect on the integrity and intrinsic motivation of employees in the DIY Police. Integrity and intrinsic motivation have been shown to play a role as mediators in the relationship between selection quality and competence. Specifically, the quality of good selection increases integrity and intrinsic motivation, which in turn contributes to the improvement of employee competence. However, the quality of selection does not have a direct effect on competence, but through an indirect influence through these mediation variables. These findings confirm the importance of proper selection in improving employee competencies through increased integrity and intrinsic motivation. The conclusion of this study is that the quality of selection has a positive effect on integrity and intrinsic motivation, which in turn improves employee competence. The influence of selection quality on competence occurs indirectly through the mediation of integrity and intrinsic motivation.